FLOW HYDROGRAPH GENERATION FOR MELAWI SUB-WATERSHED USING THE SNYDER SYNTHETIC UNIT HYDROGRAPH MODEL - Muslim, Alfin Islami Ibnu; Soeryamassoeka, S. B.; Nirmala, Azwa (Fakultas Teknik Universitas Tanjungpura, 2024)
The study, titled